Gas shielded metal arc welded joint and method for manufacturing same
By adding an appropriate amount of nitrogen to high-Mn steel welding and controlling the nitrogen content of the welding wire, and using a specific shielding gas for gas-shielded metal arc welding, the problem of complicated adjustment of high-Mn steel welding materials is solved, high-strength and extremely low-temperature toughness welded joints are achieved, and construction management is simplified.
Patent Information
- Application Number
- CN202380095824.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-28
- Filing Date
- 2023-10-31
- Publication Date
- 2025-10-17
Smart Images

Figure CN120813447A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a gas shielded metal arc welded joint of a steel material formed using a protective gas and a solid wire, and a method for manufacturing the same, and particularly to a gas shielded metal arc welded joint of a high Mn-containing austenitic steel material that can be used in an extremely low temperature environment and a method for manufacturing the same. BACKGROUND
[0002] In recent years, regulations on the environment have become increasingly strict. Among them, liquefied natural gas (hereinafter also referred to as LNG) is considered a green fuel that does not generate atmospheric pollutants such as sulfides and sulfur oxides because it does not contain sulfur, and its demand is increasing. Also, for the transportation or storage of LNG, a container (tank) that transports or stores LNG is required to maintain excellent extremely low temperature impact toughness at a temperature of -162°C or lower, which is the liquefaction temperature of LNG.
[0003] From the necessity of maintaining this excellent extremely low temperature impact toughness, as a material for a container (tank) or the like, an aluminum alloy, a 9% Ni steel, an austenitic stainless steel, or the like has been used in the past.
[0004] However, the aluminum alloy has a low tensile strength, and thus it is necessary to design the plate thickness of a structure to be large, and there is a problem of low weldability. In addition, the 9% Ni steel requires the use of an expensive Ni-based material as a welding material, which is economically disadvantageous. In addition, the austenitic stainless steel has problems of being expensive and having a low base material strength.
[0005] Due to such problems, as a material for a container that transports or stores LNG, the application of a high Mn-containing steel material (hereinafter also referred to as "high Mn steel") containing Mn in the range of 10 to 35 mass% has been recently studied. The high Mn steel has the following characteristics: even at an extremely low temperature, the metal structure is an austenite phase, brittle failure does not occur, and it has a high strength compared to an austenitic stainless steel. However, the high Mn steel base material increases the strength through work hardening based on rolling. On the other hand, at a welded portion, since it is not affected by work hardening based on rolling, the strength is lower than that of the base material, and there is a problem that the strength of the welded portion cannot be sufficiently exhibited as the original strength of the high Mn steel. Therefore, it is desired to develop a welding material and a welding technique that can realize a welded portion having a strength equivalent to that of the high Mn steel base material.
[0006] For example, Patent Literature 1 discloses a method of controlling the dilution rate of a steel material to a welded metal by adjusting the chemical composition of a welding material (solid wire) and welding conditions with respect to the chemical composition of a high Mn steel material, thereby making the strength and the extremely low temperature impact toughness of the welded portion satisfy given values.
[0007] PRIOR ART DOCUMENTS
[0008] PATENT LITERATURE
[0009] Patent Literature 1: International Publication No. 2020 / 203335 SUMMARY
[0010] PROBLEMS TO BE SOLVED BY THE INVENTION
[0011] However, in the technology described in Patent Literature 1, a welding material corresponding to the high Mn steel material needs to be selected. From such a viewpoint, considering the cost, process of manufacturing the welding material, it is difficult to design / manufacture the welding material corresponding to the different steel materials each time. In addition, since the welding conditions need to be controlled in detail, there is a problem that the welding construction management becomes complicated.
[0012] An object of the present application is to solve the above problems, and to provide a gas shielded metal arc welded joint of high Mn steel and a manufacturing method thereof, which does not require fine component adjustment of welding wire, adjustment of welding conditions, is simple, has high strength, and has excellent very low temperature toughness.
[0013] METHOD FOR SOLVING THE PROBLEMS
[0014] The inventors and others have conducted intensive research on the influence of various elements on the properties of the welded metal portion in order to achieve the above object, and have found that nitrogen (N) is particularly effective as an element that can be added to the welded portion in addition to the base material and the welding material (solid welding wire) and contributes to the improvement of strength. In addition, the following insight has been obtained: when the N content in the welded metal is increased, it has the effect of narrowing the solid-liquid coexistence temperature range, and can also exert the effect of suppressing high-temperature cracks generated in the welded metal portion.
[0015] Furthermore, it has been found that by making the N content of the solid welding wire greater than 0.1200 mass% and 0.4000 mass% or less, N from the solid welding wire, not nitrogen contained in the shielding gas, can be stably solid-solved in the welded metal.
[0016] The present application was completed based on such an insight and further research, and the gist thereof is as described below.
[0017] [1] A gas shielded metal arc welded joint which is formed using a shielding gas and a solid welding wire to form a welded metal, is a gas shielded metal arc welded joint of a steel material,
[0018] The above steel material is a high Mn-containing austenitic steel,
[0019] The chemical composition of the above steel material contains, in mass%:
[0020] C: 0.10% to 0.70%,
[0021] Si: 0.05% to 1.00%,
[0022] Mn: 18.0 to 30.0%,
[0023] P: 0.030% or less,
[0024] S: 0.007% or less,
[0025] Al: 0.010 to 0.070%,
[0026] Cr: 2.50 to 7.00%,
[0027] N: 0.0050 to 0.0500%,
[0028] O (oxygen): 0.0050% or less,
[0029] and optionally contains at least one selected from the group consisting of:
[0030] Mo: 0.01 to 2.00%,
[0031] V: 0.01 to 2.00%,
[0032] W: 0.01 to 2.00%,
[0033] Ni: 0.01 to 4.00%,
[0034] REM: 0.0010 to 0.0200% and
[0035] B: 0.0003 to 0.0030%,
[0036] the balance consisting of Fe and unavoidable impurities,
[0037] the above welding metal contains, in mass%:
[0038] C: 0.15 to 0.80%,
[0039] Si: 0.10 to 1.00%,
[0040] Mn: 17.0 to 30.0%,
[0041] P: 0.030% or less,
[0042] S: 0.030% or less,
[0043] Al: 0.001 to 0.100%,
[0044] Cr: 0.4 to 5.5%,
[0045] Mo: 0.01 to 3.50%,
[0046] Ni: 0.01% to 10.00%,
[0047] N: 0.0200% to 0.1500%,
[0048] and optionally contains at least one selected from the group consisting of:
[0049] V: 0.01% to 1.00%,
[0050] Ti: 0.010% to 1.000%,
[0051] Nb: 0.010% to 1.000%,
[0052] W: 0.01% to 1.00%,
[0053] Cu: 0.01% to 1.00% and
[0054] B: 0.0015% or less,
[0055] the balance consisting of Fe and inevitable impurities.
[0056] [2] The gas shielded metal arc welded joint according to the above-mentioned [1], wherein the mechanical properties of the welded metal are such that the yield stress as 0.2% yield strength is 400 MPa or more, the tensile strength is 600 MPa or more, and the Charpy impact absorbed energy V E -196 is 28 J or more.
[0057] [3] A method for manufacturing a gas shielded metal arc welded joint, which is a method for manufacturing the gas shielded metal arc welded joint according to the above-mentioned [1] or [2], the method comprising setting to either of the following [A] or [B]:
[0058] [A] setting the above-mentioned shielding gas to a gas containing 1.0% or more and less than 30.0% of nitrogen gas by volume%, and the remaining portion consisting of carbon dioxide gas and inevitable impurities; or
[0059] [B] setting the above-mentioned shielding gas to a gas containing 1.0% or more and less than 30.0% of nitrogen gas and 56.0% or more and less than 79.2% of Ar gas by volume%, and the remaining portion consisting of carbon dioxide gas and inevitable impurities.
[0060] [4] The method for manufacturing a gas shielded metal arc welded joint according to the above-mentioned [3], wherein the N content of the above-mentioned solid wire is set to 0.1200% or less by mass%.
[0061] [5] A method for manufacturing a gas shielded metal arc welded joint, which is a method for manufacturing the gas shielded metal arc welded joint of [1] or [2] above, the method comprising:
[0062] The above-mentioned shielding gas is set to a gas composed of carbon dioxide gas and inevitable impurities, or a gas composed of Ar gas, carbon dioxide gas and inevitable impurities,
[0063] The N content of the above-mentioned solid wire is set to a range of more than 0.1200% and 0.4000% or less in mass%.
[0064] Effects of the Invention
[0065] According to the present invention, as a welded joint for a high Mn steel used in an extremely low temperature environment, a welded joint capable of further improving the strength of the weld metal and further suppressing the generation of high temperature cracks can be easily manufactured, and a remarkable effect can be exerted in industry. BRIEF DESCRIPTION OF DRAWINGS
[0066] Figure 1 is a schematic view showing an example of a bevel shape in the gas shielded metal arc welded joint of the present invention.
[0067] Figure 2 is a schematic view showing an example of a test piece collection position of a Charpy impact test.
[0068] Figure 3 is a graph showing the change of 0.2% proof stress with respect to the N content in the weld metal accompanying the change of nitrogen content.
[0069] Figure 4 is a graph showing the change of tensile strength with respect to the N content in the weld metal accompanying the change of nitrogen content.
[0070] Figure 5 is a graph showing the change of 0.2% proof stress with respect to the N content in the weld metal accompanying the change of wire N content.
[0071] Figure 6 is a graph showing the change of tensile strength with respect to the N content in the weld metal accompanying the change of wire N content.
[0072] SYMBOL EXPLANATION
[0073] 1 Base material (steel material)
[0074] 2 Weld metal
[0075] 3 Layer of the weld metal
[0076] 4 High temperature crack
[0077] 5 Fusion line
[0078] 6 test piece
[0079] 7 center line of test piece
[0080] 8 V-notch position
[0081] T plate thickness DETAILED DESCRIPTION
[0082] Hereinafter, the embodiment of the present application is specifically described.
[0083] <Gas shielded metal arc welded joint>
[0084] The welded joint of the present embodiment is a welded joint for high Mn steel used in an extremely low temperature environment. The welded joint of the present embodiment is a gas shielded metal arc welded joint capable of further improving the strength of a welded metal and further suppressing the generation of a high temperature crack even without changing a base material or a welding material. That is, the welded joint of the present embodiment is a welded joint produced by gas shielded metal arc welding according to JIS Z 3001-7:2018 except for the kind of a shielding gas. In addition, the welded joint of the present embodiment has, in comparison with a general gas shielded metal arc welded joint, in a tensile test of a welded metal produced based on JIS Z 3111:2005, an average increase of 20 MPa or more in a yield stress and a tensile strength at normal temperature, a yield stress of 400 MPa or more as a 0.2% yield strength, and a tensile strength of 600 MPa or more. Note that the general gas shielded metal arc welded joint uses 99.5% or more of carbon dioxide gas or 80% Ar gas and 20% carbon dioxide gas in a shielding gas. Further, the welded joint has an excellent extremely low temperature impact toughness with an absorbed energy in a Charpy impact test at a test temperature of -196°C (hereinafter also referred to as "VE-196") of 28 J or more, and does not generate a high temperature crack.
[0085] [High Mn steel (high Mn-containing austenitic steel)]
[0086] First, the steel material that becomes the base material will be described. The steel material used is a high-Mn austenite steel. In the present embodiment, "high-Mn" of the high-Mn austenite steel means that the Mn content in the chemical composition of the steel material is in the range of 18.0 to 30.0% by mass. In addition, "austenite steel" of the high-Mn austenite steel means a steel material in which the base phase of the main phase of the metal structure is an austenite phase. That is, in the case where the crystal structure of the steel material is a body-centered cubic structure (bcc), the steel material has a possibility of brittle failure in a low-temperature environment, and thus is not suitable for use in a low-temperature environment. Therefore, when use in a low-temperature environment is assumed, the base phase of the metal structure of the steel material must be an austenite structure in which the crystal structure is a face-centered cubic structure (fcc). Note that "the base phase is an austenite phase" means that the austenite phase is 90% or more by area ratio. The remaining portion other than the austenite phase is a ferrite phase or a martensite phase, or an precipitate such as a carbide. More preferably, the austenite phase is 95% or more, and further preferably, 100%.
[0087] [Basic composition of the steel material]
[0088] Here, the chemical composition of the steel material of the present embodiment will be described below. Note that in the following description, "%" in "chemical composition" means "mass %" unless otherwise specified.
[0089] The steel material used in the present embodiment is the high-Mn steel material containing 18.0 to 30.0% of Mn described above, and as the other basic composition, the following is described. C: 0.10 to 0.70%, Si: 0.05 to 1.00%, P: 0.030% or less, S: 0.007% or less, Al: 0.010 to 0.070%, Cr: 2.50 to 7.00%, N: 0.0050 to 0.0500%, O (oxygen): 0.0050% or less. Also, the high-Mn steel has a chemical composition in which the balance is constituted by Fe, an optional composition, and unavoidable impurities. The reasons for the limitation of the chemical composition are described below.
[0090] [C: 0.10 to 0.70%]
[0091] C (carbon) is an inexpensive and important element that has an effect of stabilizing the austenite phase and improving the extremely low-temperature impact toughness. In order to obtain such an effect, the C content is set to 0.10% or more, preferably 0.20% or more, more preferably 0.25% or more, further preferably 0.30% or more, and most preferably 0.35% or more. On the other hand, if C exceeding 0.70% is contained, Cr carbide is excessively generated, and the extremely low-temperature impact toughness is reduced. Therefore, the C content is set to 0.70% or less, preferably 0.65% or less, more preferably 0.63% or less, further preferably 0.61% or less, and most preferably 0.60% or less.
[0092] [Si: 0.05% to 1.00%]
[0093] Si (silicon) is an element that functions as a deoxidizer and contributes to the high strength of the steel material through solid solution strengthening in the steel. In order to obtain such an effect, the Si content is set to 0.05% or more, preferably 0.07% or more, more preferably 0.10% or more, further preferably 0.15%, and most preferably 0.20% or more. On the other hand, if Si is contained in excess of 1.00%, the weldability is reduced. Therefore, the Si content is set to 1.00% or less, preferably 0.80% or less, more preferably 0.70% or less, further preferably 0.65% or less, and most preferably 0.60% or less.
[0094] [Mn: 18.0% to 30.0%]
[0095] Mn (manganese) is a relatively inexpensive element that has the effect of stabilizing the austenite phase and is an important element for achieving both high strength and excellent very low temperature impact toughness. In order to obtain such an effect, it is necessary to contain 18.0% or more. Therefore, the Mn content is set to 18.0% or more, preferably 20.0% or more, more preferably 22.0% or more, and further preferably 24.0% or more. On the other hand, even if it is contained in excess of 30.0%, the effect of improving the very low temperature impact toughness is saturated, and an effect commensurate with the content cannot be expected, which is economically disadvantageous. In addition, if it is contained in a large amount exceeding 30.0%, it leads to a reduction in the cut-off property, promotes Mn segregation, and promotes the occurrence of stress corrosion cracking. Therefore, the Mn content is set to 30.0% or less, preferably 29.0% or less, more preferably 28.5% or less, and further preferably 28.0% or less.
[0096] [P: 0.030% or less]
[0097] P (phosphorus) is an element that becomes the starting point of the occurrence of stress corrosion cracking by segregating at the grain boundaries as an impurity, and in the present embodiment, it is preferable to reduce the content of P as much as possible, and it is permissible as long as it is 0.030% or less. Therefore, the P content is set to 0.030% or less. It is preferably 0.028% or less, more preferably 0.024% or less, further preferably 0.020% or less, and most preferably 0.015% or less. On the other hand, although there is no lower limit to the P content, when the P content is extremely reduced to less than 0.002%, a long time is required for refining, and there is a risk of a high rise in the refining cost. Therefore, from an economic point of view, the P content is preferably set to 0.002% or more.
[0098] [S: 0.007% or less]
[0099] Sulfur (S) exists in steel as sulfide-based inclusions, reducing the ductility and cryogenic impact toughness of steel and weld metal. Therefore, it is desirable to minimize S, but a content of 0.007% or less is acceptable. Therefore, the S content is 0.007% or less, preferably 0.005% or less, and more preferably 0.004% or less. On the other hand, while there is no lower limit for the S content, reducing the S content to less than 0.0005% requires extended refining, potentially leading to increased refining costs. Therefore, from an economic perspective, the S content is preferably set to 0.0005% or more.
[0100] [Al: 0.010%~0.070%]
[0101] Al (aluminum) acts as a deoxidizer and is the most commonly used element in the deoxidation process of molten steel. To achieve this effect, the Al content is 0.010% or higher, preferably 0.020% or higher, and more preferably 0.030% or higher. On the other hand, if the Al content exceeds 0.070%, Al will be incorporated into the weld metal during welding, reducing the toughness of the weld metal. Therefore, the Al content is 0.070% or lower, preferably 0.060% or lower, and more preferably 0.050% or lower.
[0102] [Cr: 2.50%~7.00%]
[0103] Cr (chromium) is an element that stabilizes the austenite phase and effectively contributes to the improvement of extremely low temperature impact toughness and the improvement of steel strength. In addition, it is an effective element for forming a fine crystallized area. In order to obtain such an effect, the Cr content is 2.50% or more, preferably 3.00% or more, more preferably 3.30% or more, further preferably 3.50% or more, and most preferably 4.00% or more. On the other hand, if it contains more than 7.00% Cr, Cr carbides will be generated, and the extremely low temperature impact toughness and stress corrosion cracking resistance will be reduced. Therefore, the Cr content is 7.00% or less, preferably 6.80% or less, more preferably 6.50% or less, and further preferably 6.00% or less.
[0104] [N: 0.0050%~0.0500%]
[0105] N (nitrogen) is an element having an effect of stabilizing austenite phase, and is effective in improving the extremely low temperature impact toughness. In order to obtain such an effect, the N content is 0.0050% or more, preferably 0.0060% or more, more preferably 0.0070% or more, and further preferably 0.0080% or more. On the other hand, if more than 0.0500% is contained, nitrides or carbonitrides are coarsened during the manufacture of the steel material, and the extremely low temperature impact toughness is reduced. Therefore, the N content is 0.0500% or less, preferably 0.0450% or less, more preferably 0.0400% or less, and further preferably 0.0350% or less.
[0106] [O (oxygen): 0.0050% or less]
[0107] O (oxygen) exists in the form of oxide inclusions in the steel, and reduces the extremely low temperature impact toughness of the steel material. Therefore, it is preferable to reduce O (oxygen) as much as possible, but it is permissible as long as it is 0.0050% or less. Therefore, the O (oxygen) content is 0.0050% or less, preferably 0.0045% or less, and more preferably 0.0040% or less. On the other hand, there is no lower limit to the O (oxygen) content, but if the O (oxygen) content is extremely reduced to less than 0.0005%, a long time is required for refining, and there is a risk of a high refining cost. Therefore, from an economic point of view, O (oxygen) is preferably 0.0005% or more, and more preferably 0.0006% or more.
[0108] [Arbitrary optional composition of the steel material]
[0109] The above-described chemical composition is a preferable basic composition of the high Mn steel, and next, an arbitrary optional composition which is optionally contained as needed in addition to the basic composition will be shown. They are at least one of Mo (molybdenum): 0.01% to 2.00%, V (vanadium): 0.01% to 2.00%, W (tungsten): 0.01% to 2.00%, Ni (nickel): 0.01% to 4.00%, REM (rare earth element): 0.0010% to 0.0200%, and B (boron): 0.0003% to 0.0030%. The reasons for the limitation of each composition are described below.
[0110] [Mo, V, and W: 0.01% to 2.00%]
[0111] Mo, V and W are elements which contribute to the stabilization of austenite phase and also contribute to the improvement of strength of steel material and the improvement of extremely low temperature impact toughness, and at least one of them can be selected and contained as needed. In order to obtain such effects, it is preferable to contain Mo, V and W in a content of 0.01% or more, respectively. On the other hand, when Mo, V and W are contained in a content of more than 2.00% respectively, coarse carbonitride increases to become a starting point of damage, and there is a risk of reduction of extremely low temperature impact toughness. Therefore, in the case of containing Mo, V and W, it is preferable to be 2.00% or less. It is more preferable that the content of Mo, V and W is 1.70% or less, and it is further preferable to be 1.50% or less.
[0112] [Ni: 0.01% to 4.00%]
[0113] Ni is an element which contributes to the stabilization of austenite phase and strengthens the grain boundary of austenite, and is also an element which contributes to the improvement of extremely low temperature impact toughness of steel material. In order to obtain such effects, it is preferable to contain Ni in a content of 0.01% or more, more preferably 0.10% or more, and further preferably 0.20% or more. On the other hand, Ni is an expensive element, and it is economically disadvantageous to contain more than 4.00%. Therefore, it is preferable to contain Ni in a content of 4.00% or less, more preferably 3.75% or less, and further preferably 3.50% or less.
[0114] [REM: 0.0010% to 0.0200%]
[0115] REM is a rare earth element such as Sc, Y, La, Ce, and is an element which has the effect of improving the toughness of steel material and improving the ductility and the resistance to sulfide stress corrosion cracking by the mode control of inclusions. In order to obtain such effects, it is preferable to contain REM in a content of 0.0010% or more, more preferably 0.0015% or more. On the other hand, when more than 0.0200% is contained, the amount of non-metallic inclusions increases, and sometimes the toughness and the ductility and the resistance to sulfide stress cracking are reduced. Therefore, it is preferable to contain REM in a content of 0.0200% or less, more preferably 0.0180% or less.
[0116] [B: 0.0003% to 0.0030%]
[0117] B is an element which has the effect of contributing to the improvement of toughness of steel material by segregating at the grain boundary. In order to obtain such effects, it is preferable to contain B in a content of 0.0003% or more, more preferably 0.0008% or more. On the other hand, if more than 0.0030% is contained, coarse nitrides and carbides increase, and sometimes the toughness is reduced. Therefore, it is preferable to contain B in a content of 0.0030% or less, more preferably 0.0018% or less.
[0118] [Balance composition of steel material]
[0119] The balance of the chemical composition other than the above is composed of Fe and inevitable impurities. Note that, as the inevitable impurities, Ca, Mg, Ti, Nb, and Cu can be exemplified, and the total amount of these is allowed to be 0.05% or less. In addition, as long as the above basic composition and optional composition are satisfied, elements other than these can be contained, and such embodiments are included in the technical scope of the present application. Furthermore, the amount of the element(s) of the optional composition that is / are less than the lower limit does not affect the characteristics of the high Mn steel of the present embodiment, and thus is allowed as the inevitable impurities.
[0120] [Manufacturing method of high Mn steel]
[0121] Further, a preferred manufacturing method of the high Mn steel used in the present embodiment will be described. Note that, even if a manufacturing method other than the method described below is used, as long as the same high Mn steel can be obtained, the manufacturing method is not limited to the method described below.
[0122] The molten steel having the above steel composition is melted by a common melting method such as a converter, an electric furnace, and the like, and a steel material such as a billet having a given size is manufactured by a common casting method such as a continuous casting method or an ingot-billet rolling method. Note that, at the time of melting the molten steel, secondary refining based on a vacuum degassing device, a ladle refining device, or the like can be performed.
[0123] The obtained steel material is further heated, hot-rolled, and then cooled to manufacture a steel material having a given size. Note that, by heating at a temperature in the range of 1100°C to 1300°C, ending the hot-rolling at a finish rolling temperature of 790°C to 980°C, and immediately performing cooling or the like, a steel material having excellent very low temperature impact toughness can be manufactured. In addition, in order to adjust the characteristics of the steel material, a heat treatment such as annealing treatment can be further performed.
[0124] In addition, a preferred mechanical characteristic of the high Mn steel used in the present embodiment will be described. The high-strength steel material for very low temperature use having the above steel composition is preferably a steel material having a plate thickness of, for example, 5 mm to 102 mm, a yield stress (0.2% yield strength) at normal temperature of 400 MPa or more, and a Charpy impact absorbed energy (CVN) at normal temperature of 28 J or more. V E -196 In addition, the tensile strength at normal temperature is preferably 660 MPa or more, and more preferably 800 MPa or more.
[0125] [Basic composition of welded metal]
[0126] In the present embodiment, the steel material of the high Mn steel described above is joined to each other by gas shielded metal arc welding to form a welded joint having a welded metal portion formed of one or more layers of a welded metal.
[0127] The basic composition of the welded metal of the present embodiment is described below. The welded metal has a chemical composition containing C: 0.15% to 0.80%, Si: 0.10% to 1.00%, Mn: 17.0% to 30.0%, P: 0.030% or less, S: 0.030% or less, Al: 0.001% to 0.100%, Cr: 0.4% to 5.5%, Mo: 0.01% to 3.50%, Ni: 0.01% to 10.00%, N: 0.0200% to 0.1500%, and the balance consisting of Fe, optional selected elements, and unavoidable impurities. The reasons for the limitations of the chemical composition are described below.
[0128] [C: 0.15% to 0.80%]
[0129] C is an element that has the effect of increasing the strength of the welded metal through solid solution strengthening, and in addition, C stabilizes the austenite phase and improves the very low temperature impact toughness of the welded metal. In order to obtain such effects, it is necessary to contain 0.15% or more. Therefore, the C content is 0.15% or more, preferably 0.20% or more, more preferably 0.25% or more, further preferably 0.28% or more. On the other hand, if more than 0.80% is contained, carbides are precipitated, the very low temperature impact toughness is reduced, and in addition, high-temperature cracks during welding are easily generated. Therefore, the C content is 0.80% or less, preferably 0.75% or less, more preferably 0.70% or less, further preferably 0.65% or less, most preferably 0.63% or less.
[0130] [Si: 0.10% to 1.00%]
[0131] Si functions as a deoxidizer, improves the material utilization rate of Mn, and increases the viscosity of the molten metal, having the effect of stably maintaining the shape of the weld bead. In order to obtain such effects, it is necessary to contain 0.10% or more. Therefore, the Si content is 0.10% or more, preferably 0.15% or more, more preferably 0.20% or more, further preferably 0.25% or more, most preferably 0.28% or more. On the other hand, if more than 1.00% is contained, the very low temperature impact toughness of the welded metal is reduced. In addition, Si segregates at the time of solidification, generates a liquid phase at the solidification cell interface, and reduces the high-temperature crack resistance. Therefore, the Si content is 1.00% or less, preferably 0.80% or less, more preferably 0.75% or less, further preferably 0.70% or less.
[0132] [Mn: 17.0% to 30.0%]
[0133] Mn is an inexpensive element that stabilizes the austenite phase, and it is necessary to contain 17.0% or more in the present embodiment. If Mn is less than 17.0%, a ferrite phase is generated in the weld metal, and the extremely low temperature impact toughness is significantly reduced. Therefore, the Mn content is 17.0% or more, preferably 18.0% or more, and more preferably 19.0% or more. On the other hand, if Mn exceeds 30.0%, excessive Mn segregation occurs at the time of solidification, causing high temperature cracking. Therefore, the Mn content is 30.0% or less, preferably 28.0% or less, and more preferably 27.0% or less.
[0134] [P: 0.030% or less]
[0135] P is an element that causes high temperature cracking due to segregation at the grain boundaries of the crystal, and in the present embodiment, it is preferable to reduce P as much as possible, and it is permissible when P is 0.030% or less. Therefore, the P content is 0.030% or less, preferably 0.020% or less, more preferably 0.018% or less, further preferably 0.016% or less, and most preferably 0.014% or less. Note that, although there is no lower limit to the P content, excessive reduction of P poses the risk of causing a high refining cost. Therefore, the P content is preferably adjusted to 0.002% or more.
[0136] [S: 0.030% or less]
[0137] S exists in the form of a sulfide-type inclusion MnS in the weld metal. MnS becomes a starting point of damage, and therefore reduces the extremely low temperature impact toughness. Therefore, the S content is 0.030% or less, preferably 0.025% or less, more preferably 0.020% or less, and further preferably 0.017% or less. Note that, although there is no lower limit to the S content, excessive reduction of S poses the risk of causing a high refining cost. Therefore, the S content is preferably adjusted to 0.001% or more.
[0138] [Al: 0.001% to 0.100%]
[0139] Al functions as a deoxidizing agent, and has an important role in improving the viscosity of molten metal and stably maintaining the shape of a weld bead. In addition, Al narrows the temperature range of the solid-liquid coexistence region of molten metal, and is useful in suppressing the generation of high-temperature cracks in the weld metal. Such effects become significant when Al is contained at 0.001% or more, and thus the Al content is 0.001% or more, preferably 0.005% or more, and more preferably 0.010% or more. On the other hand, when Al is contained at more than 0.100%, the viscosity of molten metal becomes too high, and defects such as non-expansion of a weld bead and poor fusion increase. Thus, the Al content is 0.100% or less, preferably 0.060% or less, more preferably 0.050% or less, and further preferably 0.040% or less.
[0140] [Cr: 0.4% to 5.5%]
[0141] Cr functions as an element that stabilizes the austenite phase at extremely low temperatures, and has an effect of improving the extremely low-temperature fracture toughness of the weld metal. In addition, Cr has an effect of improving the strength of the weld metal, an effect of raising the liquidus temperature of molten metal to prevent high-temperature cracks in the weld metal during welding work, and an effect of improving the corrosion resistance of the weld metal. If the Cr content is too small, these effects cannot be obtained. In order to exhibit such effects, it is necessary to contain 0.4% or more, preferably 0.6% or more, and more preferably 0.8% or more. On the other hand, if the Cr content is too large, Cr carbides are precipitated in the weld metal, and thus the extremely low-temperature fracture toughness of the weld metal decreases, and thus it is necessary to be 5.5% or less, preferably 5.0% or less, and more preferably 4.5% or less.
[0142] [Mo: 0.01% to 3.50%]
[0143] Mo is an element that strengthens the grain boundary of austenite, and is segregated to the grain boundary to improve the strength of the weld metal. In addition, Mo has an effect of improving the strength of the weld metal by solid solution strengthening. In order to exhibit such effects, it is necessary to set the Mo content to 0.01% or more, preferably 0.30% or more, more preferably 0.50% or more, and further preferably 1.00% or more. On the other hand, if more than 3.50% is contained, it is precipitated in the form of a carbide, becomes a starting point of damage, and causes a decrease in the extremely low-temperature impact toughness. Thus, the Mo content is 3.50% or less, preferably 3.20% or less, more preferably 3.00% or less, and further preferably 2.50% or less.
[0144] [Ni: 0.01% to 10.00%]
[0145] Ni is an element that enhances the austenite grain boundary, segregates to the grain boundary, and improves the extremely low temperature impact toughness. In addition, Ni also has the effect of stabilizing the austenite phase, and thus, when the content is further increased, the austenite phase is stabilized, and the extremely low temperature impact toughness of the welded metal is improved. In order to exhibit this effect, the Ni content needs to be 0.01% or more, preferably 0.02% or more, more preferably 0.05% or more, and further preferably 1.00% or more. On the other hand, Ni is an expensive element, and it is economically disadvantageous to contain more than 10.00%. Thus, the Ni content is 10.00% or less, preferably 8.00% or less, more preferably 7.00% or less, further preferably 6.50% or less, and most preferably 6.00% or less.
[0146] [N: 0.0200% to 0.1500%]
[0147] N is an element that is inevitably mixed, and in the present embodiment, it is intentionally mixed. N, like C, is effective in contributing to the improvement of the strength of the welded metal, and stabilizes the austenite phase, contributing to the stable improvement of the extremely low temperature impact toughness. In addition, when the content of N is increased, it has the effect of narrowing the solid-liquid coexistence temperature range, and is an additive element that suppresses the generation of high-temperature cracks in the high-Mn steel. This effect becomes significant when it is contained at 0.0200% or more. Thus, the N content is 0.0200% or more, preferably 0.0500% or more, more preferably 0.0800% or more, and further preferably 0.1000% or more. On the other hand, when it is contained at more than 0.1500%, nitrides are formed, the low-temperature toughness decreases, and too much solid-solution N is formed, which can cause welding defects such as pores and pits. Thus, the N content is 0.1500% or less, preferably 0.1400% or less, and more preferably 0.1300% or less.
[0148] Note that, as a method of adding N to the welded metal, as described later, it can be a method of mixing and adding nitrogen gas to the shielding gas at the time of gas shielded metal arc welding, or a method of increasing the N content in a solid wire that is a welding material and adding it.
[0149] [Arbitrary selection composition of the welded metal]
[0150] For the welded metal of the present embodiment, the above-described composition is the basic chemical composition, and in addition to this chemical composition, at least one selected from V: 0.01% to 1.00%, Ti: 0.010% to 1.000%, Nb: 0.010% to 1.000%, W: 0.01% to 1.00%, Cu: 0.01% to 1.00%, and B: 0.0015% or less can be further selected and contained as an arbitrary selection composition as needed. The reasons for the limitation of each composition are described below.
[0151] [V: 0.01% to 1.00%]
[0152] V is a carbide-forming element that causes fine carbides to precipitate, thereby contributing to an increase in the strength of the weld metal. In order to obtain such an effect, in the case where V is contained, it is preferable to contain 0.01% or more, and more preferably 0.02% or more. On the other hand, if more than 1.00% is contained, the carbides become coarse, become a starting point of failure, and there is a risk of causing a decrease in the extremely low temperature impact toughness. Therefore, in the case where V is contained, it is preferable to set to 1.00% or less, and more preferably 0.80% or less, and further preferably 0.60% or less.
[0153] [Ti: 0.010% to 1.000%]
[0154] Ti is a carbide-forming element that causes fine carbides to precipitate, thereby contributing to an increase in the strength of the weld metal. In addition, Ti causes carbides to precipitate at the solidification cell boundaries of the weld metal, thereby contributing to the suppression of the generation of high-temperature cracks. In order to obtain such an effect, it is preferable to contain 0.010% or more of Ti, and more preferably 0.015% or more. On the other hand, if more than 1.000% of Ti is contained, the carbides become coarse, become a starting point of failure, and cause a decrease in the extremely low temperature impact toughness. Therefore, the Ti content is preferably set to 1.000% or less, and more preferably 0.800% or less, and further preferably 0.600% or less.
[0155] [Nb: 0.010% to 1.000%]
[0156] Nb is a carbide-forming element that is an element that causes carbides to precipitate, thereby contributing to an increase in the strength of the weld metal. In addition, Nb causes carbides to precipitate at the solidification cell boundaries of the weld metal, thereby contributing to the suppression of the generation of high-temperature cracks. In order to obtain such an effect, it is preferable to contain 0.010% or more of Nb, and more preferably 0.015% or more. On the other hand, if the Nb content exceeds 1.000%, the carbides become coarse, become a starting point of failure, and cause a decrease in the extremely low temperature impact toughness. Therefore, the Nb content is preferably set to 1.000% or less, and more preferably 0.800% or less, and further preferably 0.700% or less, and most preferably 0.600% or less.
[0157] [W: 0.01% to 1.00%]
[0158] W is a carbide-forming element, is an element that contributes to the strength improvement of the weld metal by precipitating carbides, and in addition, contributes to the stabilization of the austenite phase and the improvement of the extremely low temperature impact toughness. In addition, W precipitates carbides at the solidification cell boundaries of the weld metal, and contributes to the suppression of the generation of high-temperature cracks. In order to obtain such effects, it is preferable to contain 0.01% or more of W, more preferably 0.02% or more, and further preferably 0.05% or more. On the other hand, if the W content exceeds 1.00%, the carbides become coarse, become a starting point of damage, and result in a decrease in the extremely low temperature impact toughness. Therefore, the W content is preferably set to 1.00% or less, more preferably 0.80% or less, and further preferably 0.60% or less.
[0159] [Cu: 0.01% to 1.00%]
[0160] Cu is an element that stabilizes the austenite phase, and can stabilize the austenite phase even at extremely low temperatures, and improve the extremely low temperature impact toughness of the weld metal. In order to obtain such effects, the Cu content is preferably set to 0.01% or more, and more preferably 0.04% or more. On the other hand, if Cu is contained in a large amount and exceeds 1.00%, it will segregate at the time of solidification and cause high-temperature cracks at the time of welding. Therefore, the Cu content is preferably set to 1.00% or less, and more preferably 0.80% or less.
[0161] [B: 0.0015% or less]
[0162] B is an element that has an effect of contributing to the improvement of the toughness of the weld metal by segregating at the grain boundaries, and if it is contained in an amount exceeding 0.0015%, coarse nitrides and carbides increase and the toughness decreases. Therefore, the B content is preferably set to 0.0015% or less. The lower limit of the B content can be 0. More preferably, the B content is 0.0010% or less, and further preferably 0.0007% or less.
[0163] [Residual composition of the weld metal]
[0164] The balance other than the above-described chemical composition is composed of Fe and inevitable impurities. Note that, as the inevitable impurities, H, O, Mg, Ca, Zn, Re, REM, and the like can be exemplified, and the total is allowed to be 0.0100% or less. In addition, as long as the above-described basic composition and any of the optional compositions are satisfied, elements other than these can also be contained, and such embodiments are also included in the technical scope of the present application. Furthermore, the elements that contain less than the lower limit of the optional composition do not affect the characteristics of the weld metal, and are therefore allowed as the inevitable impurities.
[0165] Note that the chemical composition of the weld metal is mainly determined by the inflow ratio of the base material and the welding material such as the gas shielded metal-arc welding wire.
[0166] <Method for manufacturing gas shielded metal arc welded joint>
[0167] Next, the method for manufacturing a gas shielded metal arc welded joint according to the above embodiment will be described.
[0168] [Method of welding, welding conditions]
[0169] Examples of welding conditions and the like related to the method of gas shielded metal arc welding that can be suitably used in the method for manufacturing a gas shielded metal arc welded joint according to the present embodiment will be described. An example of a cross section of a welded metal portion of a welded joint is shown in FIG. 1. Figure 1 The plate thickness t of the steel material that becomes the base material 1 is in the range of 5 mm to 102 mm.
[0170] In the case of producing a test piece described later, the base material 1 is butted to form a V groove with a groove angle θ of 35° to 60° in accordance with JIS Z 3111:2005. As an electrode for gas shielded metal arc welding, a solid wire of 1.0 mm Φ to 1.6 mm Φ can be used. Preheating can not be performed.
[0171] Other welding conditions are implemented with a current of 180 A to 300 A (DCEP), a voltage of 20 V to 30 V, a welding speed of 10 cm / min to 25 cm / min, and a welding heat input of 16.0 kJ / cm to 50.0 kJ / cm. Here, if the current is less than 180 A, the wire cannot be sufficiently melted, and the arc becomes unstable, and if it exceeds 300 A, the movement of the droplet becomes unstable, and a large amount of spatter occurs. In addition, if the welding heat input is less than 16.0 kJ / cm, the amount of heat input is low, and the base material and the welded metal do not properly fuse, and a hump-shaped bead is formed, and if it exceeds 50.0 kJ / cm, the bead shape becomes irregular. More preferably, it is 18.0 kJ / cm to 28.0 kJ / cm. Further preferably, it is 20.0 kJ / cm to 22.0 kJ / cm. In addition, the interpass temperature is preferably set to 150°C or lower.
[0172] As the welding position, flat welding, horizontal welding, overhead welding, upward vertical welding, and the like can be exemplified. In addition, the groove shape can be a single bevel groove, a double bevel groove, a double V groove, and the like in addition to the V groove shown in FIG. 1. Figure 1 As described above, the groove angle θ is preferably set to 35° to 60°, and more preferably 40° to 55°.
[0173] Under the above welding conditions, a weld metal 2 is formed in the V groove by one or more layers of welding, and the weld metal 2 is in a form in which layers 3 of the weld metal are stacked in multiple layers. Note that, in a welding method (welding conditions) other than the present embodiment, a high-temperature crack 4 or the like can occur in a portion of the layers 3 of the weld metal. In the welding method of the present embodiment, such a high-temperature crack 4 or the like does not occur.
[0174] [Shielding gas]
[0175] In the present embodiment, as the shielding gas for gas shielded metal arc welding, a shielding gas containing 1.0% or more and less than 30.0% of nitrogen (N2) gas in vol% and the remaining portion consisting of carbon dioxide gas and unavoidable impurities is used. Alternatively, a shielding gas containing 1.0% or more and less than 30.0% of nitrogen gas and 56.0% or more and less than 79.2% of Ar gas in vol% and the remaining portion consisting of carbon dioxide gas and unavoidable impurities is used. Either of the above [A] or [B] can be selected for use. Note that, hereinafter, unless otherwise specified, "%" in the content of the gas component means "vol%".
[0176] The nitrogen (N) of the shielding gas is an element that, when solid-solved in the weld metal of the high-Mn steel, increases the strength of the weld metal and the welded joint by solid-solution strengthening. Further, when the N content in the weld metal is increased, a tendency to narrow the solid-liquid coexistence temperature range is exhibited, and the high-temperature crack sensitivity can be improved. In order to obtain such an effect, it is necessary to contain 1.0% or more of nitrogen in the shielding gas. Therefore, the nitrogen content in the shielding gas is set to 1.0% or more. Note that, 5.0% or more is preferable, and 10.0% or more is more preferable. On the other hand, if 30.0% or more of nitrogen is contained in the shielding gas, the arc becomes unstable, and a large amount of welding defects such as pores, craters, and the like are generated, and the joint characteristics deteriorate. Therefore, the nitrogen content in the shielding gas is set to less than 30.0%. Note that, 25.0% or less is preferable, and 20.0% or less is more preferable.
[0177] Next, the carbon dioxide (CO2) gas, which is the remaining portion of the shielding gas, is described. The carbon dioxide gas is a gas that is most commonly used as a shielding gas, and has the characteristics of being inexpensive and having a deep penetration depth compared to Ar gas or the like.
[0178] The above [A] shielding gas is one in which this carbon dioxide gas is used as the remaining portion gas. The content of the carbon dioxide gas in this case is the remaining portion other than the content of the above nitrogen gas (1.0% or more and less than 30.0%), and the content of the carbon dioxide gas is greater than 70.0% and is 99.0% or less.
[0179] On the other hand, as the shielding gas of [B] described above, carbon dioxide gas can be used not alone but in combination with Ar gas as an inactive gas. In the case of using the mixed gas of [B], it is generally preferable to use a gas mixed at Ar gas:carbon dioxide gas = 4: 1, which is easily available. Therefore, the content of the mixed gas of [B] other than nitrogen is also greater than 70.0% and 99.0% or less, and the contents of Ar gas and carbon dioxide gas are each 56.0% or more and less than 79.2% of Ar gas and more than 14.0% and 19.8% or less of carbon dioxide gas.
[0180] Note that the unavoidable impurities refer to gases other than nitrogen, carbon dioxide gas, and Ar gas, and examples include oxygen (O2) gas, hydrogen (H2) gas, and the like.
[0181] In addition, the gas flow rate of the shielding gas is preferably 10 L / min to 30 L / min, and more preferably 15 L / min to 25 L / min.
[0182] As described above, by using a shielding gas containing 1.0% or more and less than 30.0% of nitrogen in terms of vol%, the N content in the weld metal is 0.0200% to 0.1500%, N is solid-solved in the weld metal, and the strength of the weld metal and the welded joint can be improved.
[0183] [Basic composition of solid wire]
[0184] The welded joint of the present embodiment is a welded joint in which the above-described high Mn steel is joined to each other by a gas shielded metal arc welding method to form a weld metal portion formed of one or more layers of weld metal. As the solid wire used at this time, the preferable chemical composition is shown below. Note that in the following, "%" in the "chemical composition" of the solid wire means "mass%".
[0185] The preferable basic composition of the solid wire used in the present embodiment contains N: 0.4000% or less. The further preferable basic composition is described below. It contains C: 0.20% to 0.80%, Si: 0.15% to 1.00%, Mn: 17.0% to 28.0%, P: 0.030% or less, S: 0.030% or less, Ni: 0.01% to 10.00%, Cr: 0.4% to 4.0%, and Mo: 0.01% to 3.50%. It further has a composition containing B: less than 0.0015% and the balance consisting of Fe and unavoidable impurities. The reasons for the limitation of each chemical composition are described below.
[0186] [N: 0.4000% or less]
[0187] When conventional shielding gases based on carbon dioxide or a mixture of carbon dioxide and argon are used to increase the nitrogen content in the weld metal, since the nitrogen content in the weld metal does not increase, it is preferable to use a welding wire with an increased nitrogen content. In this case, the nitrogen content of the welding wire is preferably set to a range of greater than 0.1200% and less than 0.4000%. If the nitrogen content of the welding wire is less than 0.1200%, there is a risk that the nitrogen content in the weld metal cannot be fully increased. The nitrogen content of the welding wire is preferably greater than 0.2000%. If the nitrogen content of the welding wire exceeds 0.4000%, the amount added to the weld metal becomes excessive, and the intragranular strength is excessively enhanced compared to the grain boundary strength, resulting in failure at the grain boundaries and sometimes deteriorating low-temperature impact toughness. Therefore, when conventional shielding gases based on carbon dioxide or a mixture of carbon dioxide and argon are used, the nitrogen content is preferably set to less than 0.4000%, more preferably less than 0.3800%, and even more preferably less than 0.3600%.
[0188] However, when using the above-mentioned method of adding nitrogen to the weld metal from nitrogen gas using a shielding gas containing 1.0% or more and less than 30.0% nitrogen by volume, if the nitrogen content of the welding wire is high, the nitrogen content in the weld metal becomes excessive, potentially deteriorating the cryogenic impact toughness. Therefore, the nitrogen content of the welding wire is preferably suppressed to 0.1200% or less, more preferably 0.1100% or less, and even more preferably 0.1000% or less.
[0189] It should be noted that nitrogen in the welding wire is an element that effectively contributes to improving the intragranular strength of the weld metal and stabilizes the austenite phase, thereby contributing to a stable improvement in cryogenic impact toughness. To achieve these effects, the nitrogen content is preferably 0.0030% or more, more preferably 0.0040% or more, and even more preferably 0.0060% or more.
[0190] [C: 0.20%~0.80%]
[0191] C is an element that increases the strength of the weld metal through solid solution strengthening. Furthermore, C is an inexpensive and important element that stabilizes the austenite phase and increases the cryogenic impact toughness of the weld metal. To achieve this effect, the C content is preferably set to 0.20% or more, more preferably 0.25% or more, and even more preferably 0.28% or more. On the other hand, if the C content exceeds 0.80%, excessive carbides will be formed in the weld metal, reducing the cryogenic impact toughness and potentially causing high-temperature cracking during welding. Therefore, the C content is preferably set to 0.80% or less, more preferably 0.75% or less, even more preferably 0.70% or less, and most preferably 0.63% or less.
[0192] [Si: 0.15% to 1.00%]
[0193] Si functions as a deoxidizer, can improve the material utilization rate of Mn, and has an effect of increasing the viscosity of molten metal to stably maintain the shape of a weld bead. In order to obtain such an effect, the Si content is preferably 0.15% or more, more preferably 0.18% or more, further preferably 0.20% or more, and most preferably 0.25% or more. On the other hand, if more than 1.00% is contained, the very low temperature impact toughness of the weld metal decreases, and segregation occurs at the time of solidification, a liquid phase is generated at the solidification cell interface, and sometimes the high-temperature crack resistance deteriorates. Therefore, the Si content is preferably 0.90% or less, more preferably 0.80% or less, further preferably 0.75% or less, and most preferably 0.70% or less.
[0194] [Mn: 17.0% to 28.0%]
[0195] Mn is an inexpensive element that has an effect of stabilizing the austenite phase, but if the Mn content is less than 17.0%, ferrite phases are generated in the weld metal, and sometimes the very low temperature impact toughness significantly decreases. Therefore, the Mn content is preferably 17.0% or more, more preferably 18.0% or more, and further preferably 18.5% or more. On the other hand, if the Mn content exceeds 28.0%, the stacking fault energy rises and the resistance in deformation decreases, and therefore the strength sometimes decreases. Therefore, the Mn content is preferably 28.0% or less, more preferably 27.0% or less, and further preferably 26.0% or less.
[0196] [P: 0.030% or less]
[0197] P is an element that causes high-temperature cracks by segregating at the crystal grain boundaries, and in the present embodiment, it is preferable to reduce it as much as possible, and it can be allowed to be 0.030% or less. Therefore, the P content is preferably 0.030% or less, more preferably 0.020% or less, further preferably 0.018% or less, and most preferably 0.014% or less. On the other hand, although there is no lower limit to the P content, if the P content is extremely reduced to less than 0.002%, a long time is required for refining, and the refining cost rises. Therefore, from an economic point of view, the P content is preferably 0.002% or more.
[0198] [S: 0.030% or less]
[0199] S exists in the form of sulfide inclusions MnS in the weld metal. MnS becomes a starting point of failure, and thus sometimes lowers the extremely low temperature impact toughness. Therefore, the S content is preferably set to 0.030% or less, more preferably 0.025% or less, further preferably 0.020% or less, and most preferably 0.017% or less. On the other hand, although the lower limit of the S content is not limited, excessive reduction of S leads to an increase in refining cost. Therefore, the S content is preferably set to 0.001% or more.
[0200] [Ni: 0.01% to 10.00%]
[0201] Ni is an element that enhances the grain boundary of austenite, segregates to the grain boundary, and improves the extremely low temperature impact toughness. In addition, Ni also has an effect of stabilizing the austenite phase, and thus further increasing the content can stabilize the austenite phase and improve the extremely low temperature impact toughness of the weld metal. In order to obtain such an effect, the Ni content is preferably set to 0.01% or more, more preferably 1.00% or more. On the other hand, Ni is an expensive element, and it is economically disadvantageous to contain more than 10.00%. Therefore, the Ni content is preferably set to 10.00% or less, more preferably 8.00% or less, further preferably 7.00% or less, and most preferably 6.00% or less.
[0202] [Cr: 0.4% to 4.0%]
[0203] Cr is an element that effectively contributes to the improvement of the extremely low temperature impact toughness and the improvement of the strength of the weld metal by stabilizing the austenite phase at the extremely low temperature. In addition, Cr narrows the temperature range of the solid-liquid coexistence region of the molten metal, and effectively plays a role in suppressing the occurrence of high-temperature cracks. In order to obtain such an effect, the Cr content is preferably set to 0.4% or more, more preferably 0.8% or more, further preferably 1.0% or more, and most preferably 1.2% or more. On the other hand, if more than 4.0% is contained, Cr carbide is generated, and sometimes leads to a decrease in the extremely low temperature impact toughness. Therefore, the Cr content is preferably set to 4.0% or less, more preferably 3.5% or less, further preferably 3.2% or less, and most preferably 2.8% or less.
[0204] [Mo: 0.01% to 3.50%]
[0205] Mo is an element that enhances the austenite grain boundary, and is segregated to the grain boundary to increase the strength of the weld metal. In addition, it also has the effect of increasing the strength of the weld metal by solid solution strengthening. In order to obtain such effects, the Mo content is preferably set to 0.01% or more, more preferably 0.50% or more, further preferably 1.00% or more, and most preferably 1.50% or more. On the other hand, if more than 3.50% is contained, the effect of increasing the strength of the weld metal is limited, and it is precipitated in the form of carbide, becomes the starting point of damage, and sometimes causes a decrease in low temperature impact toughness. Therefore, the Mo content is preferably set to 3.50% or less, more preferably 3.30% or less, further preferably 3.10% or less, and most preferably 3.00% or less.
[0206] [B: less than 0.0015%]
[0207] B is one of the elements that segregate to the austenite grain boundary. In the case where 0.0015% or more of B is mixed, boron nitride is formed at the austenite grain boundary, the strength is reduced, and further the boron nitride becomes the starting point of damage, and sometimes the low temperature impact toughness is reduced. Therefore, the B content is preferably set to less than 0.0015%, more preferably 0.0010% or less, and further preferably 0.0005% or less.
[0208] [Arbitrary optional composition of solid wire]
[0209] The above chemical composition is a preferred basic composition of the wire used in the present embodiment, and in addition to the basic composition, any of the following optional compositions can be contained as needed. It is at least one selected from V: 0.01% to 0.04%, Ti: 0.01% to 0.04%, Nb: 0.01% to 0.04%, Cu: 0.01% to 1.00%, and Al: 0.002% to 0.100%. The reasons for limiting these compositions are as described below.
[0210] [V: 0.01% to 0.04%]
[0211] V is a carbide-forming element, and precipitates fine carbides, which contributes to an increase in the strength of the weld metal. In order to obtain such effects, the V content is preferably set to 0.01% or more. On the other hand, if more than 0.04% is contained, the carbides become coarse, become the starting point of cracking during wire drawing processing of the wire, and reduce the wire drawability, and sometimes reduce the manufacturability of the wire. Therefore, the V content is preferably set to 0.04% or less.
[0212] [Ti: 0.01% to 0.04%]
[0213] Ti is a carbide-forming element, and makes fine carbides precipitate, which contributes to an increase in strength of the weld metal. In addition, it makes carbides precipitate at the interface of the solidification cells of the weld metal, which contributes to suppression of generation of high-temperature cracks. In order to obtain such effects, the Ti content is preferably set to 0.01% or more, more preferably 0.02% or more. On the other hand, if the Ti content exceeds 0.04%, the carbides become coarse, which becomes a starting point of crack generation at the time of drawing processing of the solid wire, and reduces the drawability, and sometimes reduces the manufacturability of the wire. Therefore, the Ti content is preferably set to 0.04% or less, more preferably 0.03% or less.
[0214] [Nb: 0.01% to 0.04%]
[0215] Nb is a carbide-forming element, and makes carbides precipitate, which contributes to an increase in strength of the weld metal. In addition, it makes carbides precipitate at the interface of the solidification cells of the weld metal, which contributes to suppression of generation of high-temperature cracks. In order to obtain such effects, the Nb content is preferably set to 0.01% or more, more preferably 0.02% or more. On the other hand, if the Nb content exceeds 0.04%, the carbides become coarse, which becomes a starting point of crack generation at the time of drawing processing of the solid wire, and reduces the drawability, and sometimes reduces the manufacturability of the wire. Therefore, the Nb content is preferably set to 0.04% or less, more preferably 0.03% or less.
[0216] [Cu: 0.01% to 1.00%]
[0217] Cu is an element that stabilizes the austenite phase, and makes the austenite phase stable even at extremely low temperatures, which improves the extremely low-temperature impact toughness of the weld metal. In order to obtain such effects, the Cu content is preferably set to 0.01% or more, more preferably 0.10% or more, and further preferably 0.20% or more. On the other hand, if the Cu content exceeds 1.00%, the hot ductility decreases, and sometimes the manufacturability of the wire decreases. Therefore, the Cu content is preferably set to 1.00% or less, more preferably 0.70% or less, and further preferably 0.50% or less.
[0218] [Al: 0.002% to 0.100%]
[0219] Al functions as a deoxidizer, and has an important role in improving the viscosity of molten metal, stably maintaining the shape of a weld bead, and reducing the occurrence of spatter. In addition, Al increases the liquidus temperature of molten metal, which helps to suppress the occurrence of high-temperature cracks in a weld metal. In order to obtain such effects, the Al content is preferably set to 0.002% or more, more preferably 0.010% or more, and further preferably 0.020% or more. On the other hand, if more than 0.100% is contained, the viscosity of molten metal becomes too high, and defects such as an increase in spatter, non-expansion of a weld bead, poor fusion, and the like sometimes increase. Therefore, the Al content is preferably set to 0.100% or less, more preferably 0.060% or less, and further preferably 0.050% or less.
[0220] [Residual composition of solid wire]
[0221] The residual composition other than the above-described chemical composition is composed of Fe and inevitable impurities. Note that, as the inevitable impurities, H, O, Mg, Zn, Re, and the like can be exemplified, and the total amount is allowed to be 0.0100% or less. In addition, as long as the above-described basic composition and any of the optional compositions are satisfied, elements other than these can also be contained, and such embodiments are also included in the technical scope of the present application. Furthermore, elements that contain less than the lower limit of any of the optional compositions do not affect the properties of a weld metal, and are therefore allowed as inevitable impurities.
[0222] Examples
[0223] Hereinafter, the present application will be further described based on examples. Note that the following examples are merely for exemplifying and more specifically describing the present application, and do not limit the scope of the present application.
[0224] First, as a test material, a high-Mn steel material (plate thickness: 20 mm) having the composition shown in Table 1 was prepared for cryogenic use. In addition, a molten steel having the composition shown in Table 2 was melted and cast in a vacuum melting furnace, and a 100-kg ingot was obtained. After the obtained ingot was heated to 1200°C, hot rolling was performed, and then cold rolling, i.e., wire drawing, was performed, and a 1.2-mmΦ solid wire for gas shielded metal-arc welding was obtained.
[0225] The steel material of Table 1 described above was subjected to butt joining in accordance with JIS Z 3111:2005, and a 50° V-shaped groove was formed (see Figure 1 ). Then, the solid wire of Table 2 described above was used as a welding material, and gas shielded metal-arc welding of the melting electrode type was performed under welding conditions of a current of 200 A to 250 A, a voltage of 24 V to 26 V, a welding speed of 14 cm / min, and a gas flow rate of 20 L / min, and a welded joint having a weld metal in the above-described V-shaped groove was obtained. Each welding condition is shown in Table 3.
[0226]
[0227]
[0228]
[0229] [Composition analysis of weld metal]
[0230] From the weld metal portion of the welded joint, a 5 mm square block was collected from the plate thickness center and the weld center portion, and the content of each component in the weld metal was measured by the non-active gas melting-thermal conductivity method. Note that the N content was measured as the total N amount in the weld metal. The results thereof are shown in Table 4.
[0231]
[0232] [High temperature crack resistance evaluation]
[0233] After welding, a macro test piece having an observation surface of a thickness of 10 mm of a cross section perpendicular to the weld was collected from the center position in the weld direction, and the cross section of the weld metal was observed (30 times) using an optical microscope, and the presence or absence of a high temperature crack was determined. Note that, for the high temperature crack, if an opening portion was observed in the microstructure photograph of the optical microscope, it was determined to be a high temperature crack. In the case where a high temperature crack was confirmed to have occurred, the high temperature crack evaluation was "Yes". In the case where a high temperature crack was not confirmed to have occurred, the evaluation was "No".
[0234] [High temperature crack resistance evaluation]
[0235] According to the provisions of JIS Z 3111:2005, a tensile test piece (parallel portion diameter 6 mm Φ) and a Charpy impact test piece (V notch) were collected from the obtained weld metal, and a tensile test and an impact test were performed. Note that the collection position of the test piece (V notch) is shown in Figure 2 . The direction of the V notch 8 of the test piece 6 was perpendicular to the surface of the base material 1. The test piece 6 was collected in such a manner that the center line 7 of the test piece 6 passed through the position of the middle point (t / 2) of the plate thickness t of the base material 1, and the position of the V notch 8 became the position of the middle point between the fusion line 5 of the weld metal 2 (weld metal center).
[0236] Tensile test was performed for each of the three, and the average value of the obtained value, i.e., the 0.2% yield strength Rp0.2 as the yield stress and the average value of the tensile strength TS were taken as the tensile properties of the welded metal using the welding wire. Here, according to the kind of the shielding gas and the solid wire, the average of the yield stress ΔRp0.2 and the tensile strength ΔTS of the welded metal at normal temperature (25°C) was increased by 20 MPa or more, the 0.2% yield strength, i.e., the yield stress was 400 MPa or more, and the tensile strength was 600 MPa or more, and the case was evaluated as good in mechanical properties.
[0237] In addition, Charpy impact test was performed for each of the three, and the average value of the absorbed energy (A) at the test temperature: -196°C was taken as the very low temperature impact toughness of the welded metal using the welding wire. Note that the case where the absorbed energy at -196°C in the Charpy impact test was 28 J or more was evaluated as having excellent very low temperature impact toughness. V E -196
[0238] The results obtained are shown in Table 5.
[0239]
[0240] The properties of the joints produced by the general gas shielded metal arc welding in which nitrogen was not contained in the shielding gas were taken as comparative examples, and were shown as Joints No. 1, 6, 11, 13, 15, 18, 20, and 23.
[0241] The welded joints shown in the remarks as the inventive examples were all free from high temperature cracks at the time of welding, and were excellent in high temperature crack resistance. As compared with the general gas shielded metal arc welding joints in which nitrogen was not contained in the shielding gas, the average of the yield stress (0.2% yield strength) ΔRp0.2 and the tensile strength ΔTS of the welded metal at normal temperature (25°C) was increased by 20 MPa or more. In addition, excellent very low temperature impact toughness was also obtained.
[0242] Here, the difference (an increase of 20 MPa or more on average) in the 0.2% proof stress ΔRp0.2 and the tensile strength ΔTS of the welded joint produced using the shielding gas not containing nitrogen and the shielding gas containing nitrogen will be further explained based on the data of Table 5. For example, the joints No. 1 to 5 of Table 5 are joints produced using the steel No. a and the welding wire No. A. However, as for the kind of the shielding gas, the joint No. 1 is the gas of carbon dioxide gas alone not containing nitrogen, and the joints No. 2 to 5 are the gases containing 10 to 40 vol% of nitrogen. The welded metal properties of the obtained joints were investigated, and as for the 0.2% proof stress, the joint No. 1 (without nitrogen) was 403 MPa, and in contrast, the joint No. 2 (containing 10 vol% of nitrogen) was 441 MPa, and the difference was 38 MPa. In addition, as for the tensile strength, the joint No. 1 was 778 MPa, and in contrast, the joint No. 2 was 803 MPa, and the difference was 25 MPa. Further, in the case of the joint No. 3 (containing 20 vol% of nitrogen), the 0.2% proof stress was 460 MPa, and the difference from the joint No. 1 was 57 MPa. In addition, the tensile strength was 819 MPa, and the difference from the joint No. 1 was 41 MPa. Similarly, in the case of the joint No. 4 (containing 30 vol% of nitrogen), the difference in the 0.2% proof stress was 82 MPa, and the difference in the tensile strength was 52 MPa. In addition, in the case of the joint No. 5 (containing 40 vol% of nitrogen), the difference in the 0.2% proof stress was 101 MPa, and the difference in the tensile strength was 57 MPa. As described above, when nitrogen is contained in the shielding gas, the tensile strength and the 0.2% proof stress are increased in accordance with the content of nitrogen.
[0243] Note that the nitrogen content in the shielding gas of the joints No. 4, 5, 9, 10, 17 is too much, and pits and blowholes frequently occur, and it is not suitable as a welded joint.
[0244] Further, the joints No. 18 and 19 are examples of the welded joint based on the steel No. d having a chemical composition deviating from the limited range of the present application and the solid welding wire No. E having a chemical composition deviating from the preferred range, which are used in the method for producing the welded joint of the present application. In the case of the joint No. 18, since nitrogen is not contained in the shielding gas, the 0.2% proof stress preferred in the present application is not achieved. However, it is known that when nitrogen is contained in the shielding gas as in the joint No. 19, similarly to the other examples, the N content in the welded metal is increased, and the effect of increasing the strength can be obtained.
[0245] In the joint No. 24 using the welding wire No. F of the same composition as that of the joint No. 23 and with the N content increased (0.3290%), even if the shielding gas does not contain nitrogen, the N content in the welded metal is within the limited range of the present application, the difference in the 0.2% yield strength is 59 MPa, and the difference in the tensile strength is 37 MPa. In addition, the joints No. 25 and No. 26 using the shielding gas containing 20% and 40% of nitrogen have pores in the welded metal because the N content in the welded metal exceeds the upper limit of the limited range, and are improper joints.
[0246] [Relationship between nitrogen content of shielding gas or N content of welding wire and strength of welded metal]
[0247] Based on the data of Table 5 above, the changes in the 0.2% yield strength and the tensile strength with respect to the N content in the welded metal were arranged according to the method of mixing and adding nitrogen in the shielding gas as the N addition method and the method of adding by increasing the N content in the welding wire.
[0248] Figure 3 is a graph showing the change in the 0.2% yield strength with respect to the N content in the welded metal accompanying the change in the nitrogen content, Figure 4 is a graph showing the change in the tensile strength with respect to the N content in the welded metal accompanying the change in the nitrogen content. In addition, Figure 5 is a graph showing the change in the 0.2% yield strength with respect to the N content in the welded metal accompanying the change in the N content of the welding wire, Figure 6 is a graph showing the change in the tensile strength with respect to the N content in the welded metal accompanying the change in the N content of the welding wire. Here, with respect to Figure 3 and Figure 4 , the grouping was performed according to the condition of the nitrogen content of the shielding gas, and with respect to Figure 5 and Figure 6 , the grouping and arrangement were performed according to the high and low of the N content of the welding wire.
[0249] As is clear from Figure 3 , in the same combination of steel material and welding wire, when the nitrogen content in the shielding gas is changed, the 0.2% yield strength is higher in the case of containing 10% by volume than in the case of not containing nitrogen, and is further increased in the case of containing 20% by volume. Figure 4 The same is true of the tensile strength of the welded metal, and the tensile strength is increased as the nitrogen content is increased to 10% by volume and 20% by volume. Figure 5 and Figure 6 It is also clear that when the N content of the welding wire is increased, the N content in the welded metal is increased, and thereby the strength is increased. It is thereby confirmed that increasing the N content in the welded metal of the present application is effective for increasing the strength of the welded metal.
Claims
1. A gas-shielded metal arc welded joint, which is formed by using a shielding gas and a solid welding wire to form weld metal, and is a gas-shielded metal arc welded joint of steel. The steel is a high-Mn austenitic steel. The chemical composition of the steel material contains, in mass %, the following: C:0.10%~0.70%、 Si: 0.05%~1.00%, Mn: 18.0%~30.0%, P: 0.030% or less, S: 0.007% or less, Al:0.010%~0.070%、 Cr:2.50%~7.00%、 N:0.0050%~0.0500%、 O (oxygen): 0.0050% or less, And optionally contain at least one selected from the following: Mo: 0.01%~2.00%, V:0.01%~2.00%、 W:0.01%~2.00%、 Ni: 0.01%~4.00%, REM: 0.0010%~0.0200% and B:0.0003%~0.0030%, The balance consists of Fe and inevitable impurities. The chemical composition of the weld metal contains, in mass %, the following: C:0.15%~0.80%、 Si: 0.10%~1.00%, Mn: 17.0%~30.0%, P: 0.030% or less, S: 0.030% or less, Al:0.001%~0.100%、 Cr:0.4%~5.5%、 Mo: 0.01%~3.50%, Ni: 0.01%~10.00%, N:0.0200%~0.1500%, And optionally contain at least one selected from the following: V:0.01%~1.00%、 Ti: 0.010%~1.000%, Nb: 0.010%~1.000%, W:0.01%~1.00%、 Cu: 0.01%~1.00% and B: 0.0015% or less, The balance consists of Fe and inevitable impurities.
2. The gas metal arc welded joint according to claim 1, wherein: The mechanical properties of the weld metal are as follows: the yield stress as 0.2% yield strength is 400 MPa or more, the tensile strength is 600 MPa or more, and the Charpy impact absorption energy is V E -196 More than 28J.
3. A method for manufacturing a gas-shielded metal arc welded joint, the method comprising: [A] The protective gas is a gas containing, by volume, 1.0% or more and less than 30.0% nitrogen gas, with the remainder being carbon dioxide gas and unavoidable impurities; or [B] The protective gas is a gas containing, by volume%, 1.0% to less than 30.0% of nitrogen gas and 56.0% to less than 79.2% of Ar gas, with the remainder being carbon dioxide gas and unavoidable impurities.
4. The method for manufacturing a gas shielded metal arc welded joint according to claim 3, wherein: The N content of the solid wire is set to 0.1200% or less in mass %.
5. A method for manufacturing a gas-shielded metal arc welded joint, which is a method for manufacturing the gas-shielded metal arc welded joint according to claim 1 or 2, the method comprising: The protective gas is a gas composed of carbon dioxide gas and inevitable impurities, or a gas composed of Ar gas, carbon dioxide gas and inevitable impurities. The N content of the solid wire is set to be within a range of greater than 0.1200% and not more than 0.4000% in terms of mass %.
Citation Information
Patent Citations
Method for producing high-strength welded joint for cryogenic environments
WO2020203335A1
Cited By
Nanometer composite precipitation strengthening austenite superhard steel and preparation method thereof
CN121992313A
A nanocomposite precipitation-strengthened austenitic superhard steel and its preparation method
CN121992313B